Courage and Love in Badiou's Beckett - Storey, Graham (Cosmos and History: The Journal of Natural and Social Philosophy, 2006)
Reviw of Alain Badiou,On Beckett, ed. and trans. Nina Power and Alberto Toscano, Clinamen Press, Manchester, 2003. ISBN: 1903083 30 Badiou's remarkable reading of Beckett seeks to deliver the work of this great writer from the grasp of existentialist phenomenological readings. However, I argue that Badiou#39;s reading of Beckett opens the way for a deeper consideration of the existential issues embedded in Badiou's own work and that this is most fruitfully approached by recalling the thought of Sartre.